THE ROLE OF THE GOVERNMENT IN DETERMINING THE PURCHASE PRICE OF OIL PALM FRESH FRUIT BUNCHES IN CENTRAL MAMUJU REGENCY - Ritu, Susan; Sakawati, Herlina; Nur, Andi Cudai; Purna, Zarni Adia (Jurnal Aktor, 2025)
This study aims to determine the role of the government in determining the purchase price of oil palm fresh fruit bunches in Central Mamuju district and government obstacles in determining the purchase price of oil palm fresh fruit bunches in Central Mamuju district. This research is a qualitative research with 4 informants. Data collection was carried out using observation, interview and documentation techniques. The data analysis technique used consists of data condensation, data presentation and conclusion drawing.The results of this study indicate that the role of the government in determining the purchase price of oil palm fresh fruit bunches in Central Mamuju district can be seen from three roles: 1) as a regulator, 2) as a stabilizer, 3) as a dynamizer has played a good role in regulating, supervising and maintaining the stability of FFB prices. There are several obstacles to the role of the government in setting FFB prices, namely oil palm companies that do not comply with the price policy set, farmers' understanding of the rules that are still lacking and cooperation and support from the government that is less than optimal.